The Records of John Glassford and Company Containers 152-154
Ledgers, journals, daybooks, inventories, cashbooks of the various mercantile firms in Maryland and Virginia representing or succeeding the Glasgow, Scotland, firm of John Glassford and Company in the Chesapeake tobacco trade.